True to Our Roots - Dolan, Paul; Dolan, Paul (Bloomberg Press, 2003)
True to Our Roots sets forth the simple but powerful management principles that enabled Fetzer Vineyards under Paul Dolan to become one of America$1 (Bs biggest and best-known wineries even as it was turning into a model for sustainable businesses everywhere. Today, Dolan and Fetzer are leading the California wine industry toward profound change in how wineries and grape growers preserve their environment, strengthen their communities, and enrich the lives of their employees, without sacrificing the bottom line. This is truly a management revolution in one of the most globalized, competitive industries on Earth. The principles Dolan discovered and developed at Fetzer can be applied to any business and by leaders at every level: A business is part of a much larger system A company$1 (Bs culture is determined by the context created for it The soul of a company is found in the hearts of its people The future can$1 (Bt be predicted, but it can be created There is a way to make an idea$1 (Bs time come Filled with personal anecdotes and practical wisdom, this book offers inspiration and guidance to business managers who see the compelling need to build and grow healthy, sustainable organizations. For all readers, True to Our Roots provides both a fascinating glimpse into the California wine industry and heartening proof that business can do well by doing good.s